2022
DOI: 10.1093/pm/pnac127
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Tuina in Relieving Pain, Negative Emotions, and Disability in Knee Osteoarthritis: A Randomized Controlled Trial

Abstract: Objective To evaluate the effectiveness of Tuina in relieving the pain, negative emotions, and disability of patients with knee osteoarthritis (KOA). Design Single-centre, parallel, randomized controlled trial. Setting Shanghai Guanghua Integrated Chinese and Western Medicine Hospital, Shanghai, China. Subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…These points in TCM theory are interpreted as tonifying Qi and Blood, promoting the circulation of meridian channels and collaterals, leading to facilitating joint function recovery. Previous RCTs have also con rmed that acupoint stimulation around the knee joint has a signi cant effect on KOA and improves patients' pressure-pain threshold [53,55], which was consistent with the ndings of our previous study [39]. This multicenter pilot study expands patient recruitment beyond a single hospital setting to minimize regional differences that may exist.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These points in TCM theory are interpreted as tonifying Qi and Blood, promoting the circulation of meridian channels and collaterals, leading to facilitating joint function recovery. Previous RCTs have also con rmed that acupoint stimulation around the knee joint has a signi cant effect on KOA and improves patients' pressure-pain threshold [53,55], which was consistent with the ndings of our previous study [39]. This multicenter pilot study expands patient recruitment beyond a single hospital setting to minimize regional differences that may exist.…”
Section: Discussionsupporting
confidence: 89%
“…The calculation of sample size was based on the hypothetical changes in the outcome measurement, WOMAC pain subscale, at week 4. According to our previous clinical trial [39], we formulate expected effects with WOMAC pain subscale as the primary outcome. We hypothesized that a 2-point improvement in WOMAC pain subscale occurred in the Tuina group.…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Glx is also involved in mood regulation. A study has shown that tuina can relieve the negative emotions in pain patients (Xu et al, 2022), suggesting that tuina may reduce pain sensitivity by improving negative emotions. Zhang et al (2014) found that the levels of gama amino-butyrlcacid (GABA) and GABAAR in the periaqueductal gray and rostral ventromedial medulla of CCI rats increased after pressing and kneading the "Huantiao" (GB30).…”
Section: Tuina Exerts Analgesic Effects By Adjusting the Functional A...mentioning
confidence: 99%
“…When carrying out tuina, mechanical force stimulation can be transmitted to blood vessels and nerve tissues, thereby altering the neuroendocrine system and blood circulation [29]. This enhances the function of the brain area responsible for controlling mood and sleep state, and several studies have substantiated this claim [30][31][32][33][34][35]. Moreover, conscious and autonomous tuina could help drug abusers rewire their brains, foster new neural connections, and gradually decrease their urge to use drugs [36].…”
Section: Introductionmentioning
confidence: 99%